2013
DOI: 10.1371/journal.pgen.1003645
|View full text |Cite
|
Sign up to set email alerts
|

The Wilms Tumor Gene, Wt1, Is Critical for Mouse Spermatogenesis via Regulation of Sertoli Cell Polarity and Is Associated with Non-Obstructive Azoospermia in Humans

Abstract: Azoospermia is one of the major reproductive disorders which cause male infertility in humans; however, the etiology of this disease is largely unknown. In the present study, six missense mutations of WT1 gene were detected in 529 human patients with non-obstructive azoospermia (NOA), indicating a strong association between WT1 mutation and NOA. The Wilms tumor gene, Wt1, is specifically expressed in Sertoli cells (SCs) which support spermatogenesis. To examine the functions of this gene in spermatogenesis, Wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 57 publications
4
92
0
Order By: Relevance
“…To trace the origin of 3β-HSD-positive cells in Wt1-deficient gonads, a WT1 and 3β-HSD double staining experiment was performed. Our previous studies demonstrated that although the small truncated WT1 protein remaining after the deletion of two exons from the Wt1 flox allele had lost its function, it was still recognized by the antibody used in this study and could be used to trace the Wt1 mutant cells (Gao et al, 2006;Hu et al, 2011;Wang et al, 2013). We found that most 3β-HSD-positive cells were also positive for WT1 (Fig.…”
Section: Wt1mentioning
confidence: 54%
“…To trace the origin of 3β-HSD-positive cells in Wt1-deficient gonads, a WT1 and 3β-HSD double staining experiment was performed. Our previous studies demonstrated that although the small truncated WT1 protein remaining after the deletion of two exons from the Wt1 flox allele had lost its function, it was still recognized by the antibody used in this study and could be used to trace the Wt1 mutant cells (Gao et al, 2006;Hu et al, 2011;Wang et al, 2013). We found that most 3β-HSD-positive cells were also positive for WT1 (Fig.…”
Section: Wt1mentioning
confidence: 54%
“…However, no WT1 signal was detected in the tumor cells from double KO mice (Fig. 1F), despite the fact that it has been demonstrated that the small truncated WT1 protein remaining after the deletion of two exons from the Wt1 flox allele is recognized by the antibody used in this study and can be used to trace Wt1 mutant Sertoli cells (13,16). Surprisingly, the Leydig cell-specific marker genes 3β-HSD and P450SCC were abundantly expressed in double KO tumor cells ( (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…NOA is a heterogeneous disorder caused by complex genetic and environmental factors. Hereditary changes, including chromosome abnormalities and gene mutations, have been implicated in NOA (4)(5)(6); however, the etiology of this disease remains largely unclear.…”
mentioning
confidence: 99%